Pelvic Sarcoma Treated with Extended Total Exenteration and Prosthetic Arterial and Venous Reconstruction - Case Report - Johnson, Luis Fernando Pinto (2001)
We describe a case of a patient with pelvic sarcoma submitted to extended total pelvic exenteration including left testicle and left external iliac vessels with arterial and venous prosthetic reconstruction. The impact of the complete resection in the overall survival is emphasized because neither radiotherapy or chemotherapy have had better results than surgery alone or associated in low grade retroperitoneal sarcoma. Vessel resection is not frequently done for this tumor but can be necessary to achieve an adequate resection and limb - salvage, rising the overall survival of this patients. The optimal reconstruction remains unclear when vein is resected but good results can be achieved with prosthetic material.